PROTAC: a revolutionary technology propelling small molecule drugs into the next golden age - Cai, Jiale; Chen, Chen; Wang, Jiayue; Zhang, Xinmeng; Cui, Yuqiu; Zhu, Qunshan; Sun, Haibo (Frontiers in Oncology, 2025)
Proteolysis Targeting Chimera (PROTAC) is a heterobifunctional molecule comprising three core components: a target protein ligand (typically a small-molecule inhibitor), a linker, and an E3 ubiquitin ligase ligand. By harnessing the specificity of the endogenous ubiquitin-proteasome system (UPS), PROTACs induce ubiquitination and subsequent degradation of target proteins. This technology constitutes an advanced therapeutic strategy for selective protein degradation, thereby expanding the horizons of drug design. Its significant therapeutic potential extends to treating cancers, viral infections (e.g., HIV and SARS-CoV-2), and chronic diseases. Recent clinical studies on compounds such as ARV-471 have yielded encouraging results, validating the efficacy of this approach. Over the past decade, PROTAC technology has garnered widespread attention in biomedicine for its promise in developing novel targeted therapies. This review will elucidate the broad therapeutic prospects and future challenges of PROTACs by detailing their mechanism of action, recent advances, progress in targeted therapy research, and current clinical trial landscape.